The Influence of Service Quality and Brand Equity on Attitude and Behavior Loyalty on Bank Jatim Syariah Surabaya Branch - Nurul Kamaril; Nurul Aini; Joko Suyono; Damarsari Ratnasahara (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This paper aims to analyze the influence of service quality and brand equity on attitude and behavior loyalty in the customers from Bank Jatim Syariah Surabaya.